Neuroimaging studies to understand neural mechanisms of pain in osteoarthritis - Reckziegel, Diane (2017)
Osteoarthritis pain is a major cause of long-term disability and chronic pain in the adult population, which can lead to reduced quality of life and serious comorbidities such as depression. Together with the substantial burden chronic osteoarthritis pain (COAP) causes at the individual level, associated economical costs are alarming and set to rise given the ageing population. Yet there are very few effective treatments available, which include both pharmacological and non-pharmacological options. Around one in five COAP patients do not receive satisfactory pain relief, even after undergoing joint replacement surgery. This strongly supports the notion that chronic osteoarthritis pain has a central component, and reflects the need for improved understanding of neural mechanisms of chronic pain and chronic pain relief.